The molecular dimension of microbial species: 1. Ecological distinctions among, and homogeneity within, putative ecotypes of Synechococcus inhabiting the cyanobacterial mat of Mushroom Spring, Yellowstone National Park - Becraft, Eric D.; Wood, Jason M.; Rusch, Douglas B.; Kühl, Michael; Jensen, Sheila I.; Bryant, Donald A.; Roberts, David W.; Cohan, Frederick M.; Ward, David M. (Frontiers in Microbiology, 2015)
Based on the Stable Ecotype Model, evolution leads to the divergence of ecologically distinct populations (e.g., with different niches and/or behaviors) of ecologically interchangeable membership. In this study, pyrosequencing was used to provide deep sequence coverage of Synechococcus psaA genes and transcripts over a large number of habitat types in the Mushroom Spring microbial mat. Putative ecological species (putative ecotypes), which were predicted by an evolutionary simulation based on the Stable Ecotype Model (Ecotype Simulation), exhibited distinct distributions relative to temperature-defined positions in the effluent channel and vertical position in the upper 1 mm-thick mat layer. Importantly, in most cases variants predicted to belong to the same putative ecotype formed unique clusters relative to temperature and depth in the mat in canonical correspondence analysis, supporting the hypothesis that while the putative ecotypes are ecologically distinct, the members of each ecotype are ecologically homogeneous. Putative ecotypes responded differently to experimental perturbations of temperature and light, but the genetic variation within each putative ecotype was maintained as the relative abundances of putative ecotypes changed, further indicating that each population responded as a set of ecologically interchangeable individuals. Compared to putative ecotypes that predominate deeper within the mat photic zone, the timing of transcript abundances for selected genes differed for putative ecotypes that predominate in microenvironments closer to upper surface of the mat with spatiotemporal differences in light and O2 concentration. All of these findings are consistent with the hypotheses that Synechococcus species in hot spring mats are sets of ecologically interchangeable individuals that are differently adapted, that these adaptations control their distributions, and that the resulting distributions constrain the activities of the species in space and time.